P2O5-Al2O3 Catalyzed One Pot Acetylation, Benzylidene Acetal Protection and Benzylidene Removal of Sugar Derivatives - Sharma, Anjali; Panchadhayee, Rajib (Asian Journal of Chemistry, 2023)
An environment-friendly, simple and efficient one-pot acetylation and benzylidene acetal formation procedure has been introduced for the synthesis of sugar derivatives using P2O5-Al2O3 as a solid acid catalyst under solvent-free condition at room temperature, with excellent overall yield. This benzylidene acetal has been deprotected using the same reagent but in a moist condition.